Evaluación de la actividad antioxidante e hipoglucemiante de un jarabe de extracto acuoso de hojas de Chaya (Cnidoscolus aconitifolius) libre de glucósidos cianogénicos - Luna Iñiguez, Verónica M. (2014)
Chaya (Cnidoscolus aconitifolius (Mill.) I. M. Johnst.) is a medicinal and nutritional source recognized by our population. However, its use is limited due to its high content of cyanogenic glycosides, toxic and antinutricional compounds.